Alloy formation during the electrochemical growth of a Ag-Cd ultrathin film on Au(1 1 1) - del Barrio, Maria Cecilia (2009)
The electrodeposition of a Ag/Cd ultrathin film on a Au(1 1 1) surface and the formation of a surface alloy during this process have been studied using classical electrochemical techniques and in situ Scanning Tunneling Microscopy (STM). The films were obtained from separate electrolytes containing Ag+ or Cd2+ ions and from a multicomponent solution containing both ions. First, the polarization conditions were adjusted in order to form a Ag film by overpotential deposition. Afterwards, a Cd monolayer was formed onto this Au(1 1 1)/Ag modified surface by underpotential deposition. The voltammetric behavior of the Cd UPD and the in situ STM images indicated that the ultrathin Ag films were uniformly deposited and epitaxially oriented with respect to the Au(1 1 1) surface. Long time polarization experiments showed that a significant Ag-Cd surface alloying accompanied the formation of the Cd monolayer on the Au(1 1 1)/Ag modified surface, independent of the Ag film thickness. In the case of an extremely thin Ag layer (1 Ag ML) the STM images and long time polarization experiments revealed a solid state diffusion process of Cd, Ag, and Au atoms which can be responsible for the formation of different Ag-Cd or Au-Ag-Cd alloy phases. © 2009 Elsevier Ltd. All rights reserved.